An Invited Commentary "Prognostic effect of the new 5-factor modified frailty index in patients undergoing carotid endarterectomy with regional anesthesia - A prospective cohort study". (September 2020) - Chen, Hualei; Atogebania, Julius Wedam
Abstract: Frailty has been studied as a valuable predictor of adverse health events and poor postoperative outcomes in patients undergoing surgery. Thus, the use of simple and adapted indexes to define frailty, like the modified frailty index (Mfi)-11, proved useful in assessing patients undergoing vascular surgery. The role of carotid endarterectomy (CEA) continues to be debated in the age of optimal medical therapy, particularly for patients with limited life expectancy (Rothenberg et al., 2020) [3]. The Risk Analysis Index (RAI) measures frailty, a syndrome of decreased physiologic reserve, which increases vulnerability to adverse outcomes. However, the literature about the applicability of an even more pragmatic index, the modified frailty (mFi) index mFI-5 in vascular patients is scarce, particularly in those submitted to carotid endarterectomy (CEA). This study aimed to validate and estimate the prognostic value of the mFI-5 on the postoperative period and long-term survival of this population (Araújo-Andrade et al., 2020) [1].